MSP: An emerging player in metabolic syndrome. Issue 1 (February 2015) - Li, Jieyi; Chanda, Dipanjan; Shiri-Sverdlov, Ronit; Neumann, Dietbert
Highlights: MSP is a key negative regulator in inflammation in multiple disease models. MSP has potential beneficial effects in regulation of lipid and glucose metabolism. MSP may possibly act as a crucial regulator of metabolic syndrome. Abstract: MSP (Macrophage Stimulating Protein; also known as Hepatocyte Growth Factor-like protein (HGFL) and MST1) is a secreted protein and the ligand for transmembrane receptor tyrosine kinase Recepteur d'Origine Nantais (RON; also known as MST1R). Since its discovery, MSP has been demonstrated to play a key role in regulating inflammation in the peripheral tissues of multiple disease models. Recent evidences also point toward a beneficial role of MSP in the regulation of hepatic lipid and glucose metabolism, thereby implicating MSP as a crucial regulator in maintaining metabolic homeostasis while simultaneously suppressing inflammatory processes. In this review, we discuss the recent advances that demonstrate the significance of MSP in metabolic syndrome and build a strong case supporting its therapeutic potential.